Emma [videorecording (DVD)] : a Victorian romance. Season 2, disc 1 - Mori, Kaoru, 1978- (Nozomi Entertainment, 2008)
The love story, and the complications that result, when Emma, a maid and William, a member of the gentry class fall for each other. Now that Emma is faraway, William is being comforted by Eleanor, who could be the answer to his broken heart.